Hyperconfined bio-inspired polymers in integrative flow-through systems for highly selective removal of heavy metal ions - Nakahata, Masaki; Sumiya, Ai; Ikemoto, Yuka; Nakamura, Takashi; Dudin, Anastasia; Schwieger, Julius; Yamamoto, Akihisa; Sakai, Shinji; Kaufmann, Stefan; Tanaka, Motomu (Nature Communications, 2024)
Access to clean water, hygiene, and sanitation is becoming an increasingly pressing global demand, particularly owing to rapid population growth and urbanization. Phytoremediation utilizes a highly conserved phytochelatin in plants, which captures hazardous heavy metal ions from aquatic environments and sequesters them in vacuoles. Herein, we report the design of phytochelatin-inspired copolymers containing carboxylate and thiolate moieties. Titration calorimetry results indicate that the coexistence of both moieties is essential for the excellent Cd2+ ion-capturing capacity of the copolymers. The obtained dissociation constant, KD ~ 1 nM for Cd2+ ion, is four-to-five orders of magnitude higher than that for peptides mimicking the sequence of endogenous phytochelatin. Furthermore, infrared and nuclear magnetic resonance spectroscopy results unravel the mechanism underlying complex formation at the molecular level. The grafting of 0.1 g bio-inspired copolymers onto silica microparticles and cellulose membranes helps concentrate the copolymer-coated microparticles in ≈3 mL volume to remove Cd2+ ions from 0.3 L of water within 1 h to the drinking water level (<0.03 µM). The obtained results suggest that hyperconfinement of bio-inspired polymers in flow-through systems can be applied for the highly selective removal of harmful contaminants from the environmental water.
Gesehen am 03.02.2025